Does Religiosity Predict Blood Donation in Brazil? - Zucoloto, Miriane (Journal of religion and health, 2022)
The aim of this study was to investigate the association of religiosity with blood donation in a representative/stratified sample of primary healthcare users of Ribeirão Preto, São Paulo, Brazil. A cross-sectional study was conducted using the Duke University Religious Index—DUREL (dimensions: organizational, non-organizational, and intrinsic religiosity). Odds ratios adjusted by sex and age were used as measures of association. A total of 1055 individuals participated (79.7% females; mean age = 40.6 years); 23.3% had previously donated blood. Most reported having a religion and grew up in a religious environment. High frequencies of religiosity were observed. Similar DUREL scores were observed among participants who donated blood and those who did not. Family members and close friends had significant influence on participants’ blood donation practices. Religiosity was not directly associated with blood donation despite the high prevalence and scores of religiosity. However, possible associations between religion and blood donation should consider mediating variables in future studies.